Listening Strategies Introduced at A Language Institute - Safitri, Hilma (Jurnal Ilmiah Humanika, 2018)
This study looked at the listening strategies introduced The object of the study was seven classes of English for Adults (EA) of various levels at LBPP-LIA Kalimalang, Jakarta. The sources of data comprised the activities in the classrooms during a listening session which included the spoken exchanges between all participants (students and the teachers). Data collection consisted of audio recording of the spoken exchanges and note taking of all observed activities during the listening session. The analysis on the listening strategies introduced in the seven observed classes was carried out using Vandergrift‘s (Flowerdew and Miller: 2005) classification of listening strategies. It was found that the dominance of listening strategy used was Double-Check Monitoring (33.98%). It was followed by Direct Attention, Selective Attention, and Extralinguistic Inferencing as the second most frequently introduced (11.65%). Cooperation was the third (9.7%). The fourth was Self-Management and Auditory Monitoring (5.83%) respectively. Linguistic Inferencing and Inferencing between Parts took the fifth (1.94%).The least introduced listening strategies were Creative Elaboration and Summarization (0.97%) for each. In other words, the percentage of Vandergrift‘s listening strategy which are classified into Metacognitive, Cognitive and Socioaffective strategies were 86.94%, 21.35% and 9.7% respectively. The observed strategies were introduced by the teachers to get immediate feedback on the students‘ comprehension, to help the students understand the listening materials, and to motivate the students to listen. The teachers seemed to be aware that to introduce listening strategies was necessary to facilitate the students‘ listening to achieve comprehension. However, the ways the teachers introduced the listening strategies could have been more varied in order to maintain the students‘ interest and participation.